Exercise-induced hypoalgesia in chronic neck pain: A narrative review - Fernando Rojas-Galleguillos; Cecilia Clark-Hormazábal; Eduardo Méndez-Fuentes; Francisco Guede-Rojas; Cristhian Mendoza; Andrés Riveros Valdés; Claudio Carvajal-Parodi (Sports Medicine and Health Science, 2024)
Chronic neck pain (CNP) is a worldwide health problem with several risk factors. One of the most widely used treatments for managing this condition is therapeutic exercise, which could generate a response called exercise-induced hypoalgesia (EIH). There is no consensus on the best exercise modality to induce hypoalgesia. Therefore, this review aims to analyze and synthesize the state-of-the-art about the hypoalgesic effect of exercise in subjects with CNP. We included articles on EIH and CNP in patients older than 18 years, with pain for more than three months, where the EIH response was measured. Articles that studied CNP associated with comorbidities or measured the response to treatments other than exercise were excluded. The studies reviewed reported variable results. Exercise in healthy subjects has been shown to reduce indicators of pain sensitivity; however, in people with chronic pain, the response is variable. Some investigations reported adverse effects with increased pain intensity and decreased pain sensitivity, others found no clinical response, and some even reported EIH with decreased pain and increased sensitivity. EIH is an identifiable, stimulable, and helpful therapeutic response in people with pain. More research is still needed on subjects with CNP to clarify the protocols and therapeutic variables that facilitate the EIH phenomenon. In addition, it is necessary to deepen the knowledge of the intrinsic and extrinsic factors that influence EIH in people with CNP.